Penurunan Kadar TSS Dan COD Limbah Cair Rumah Pemotongan Hewan Menggunakan Elektrolisis - Ledoh, Sherlly M. F.; Dasul, Aprilia R. T.; Ola, Pius D.; Ola, Antonius R. B. (Universitas Nusa Cendana, 2022)
Research has been carried out on Reducing COD and TSS Levels of Slaughterhouse Liquid Waste Using the Electrolysis Method. This study aims to analyze the effect of electrolysis time and voltage (voltage) on the reduction of COD and TSS levels of RPH waste water using the electrolysis method. Electrolysis is the decomposition of electrolytes by direct electric current using two kinds of electrodes as conductors of electric current. The results showed that the longer the electrolysis time and the greater the voltage, the percentage of reduction in COD and TSS levels increased. The percentage reduction obtained was 31.43% COD and 95% TSS at 120 minutes of electrolysis time and 12 volts of voltage.